The effect of phosphoric acid application time on the bond strength of orthodontic brackets - Mitić Vladimir; Janošević Mirjana (Serbian Medical Society - Dental Section, Belgrade, 2008)
Aim: The aim of this study was to evaluate the effect of different surface treatment intervals (15, 30 and 45 s) of 37% phosphoric acid on the bond strength of orthodontic brackets. Materials and Methods: Seventy extracted premolars, glass ionomer cement Ortho Fuji LC (GC Inc., Tokyo, Japan) and a conventional self-curing adhesive, System 1+ (Dentaurum, Inspringen, Germany) were used. Results: The obtained results suggested that the strongest bond was accomplished after enamel conditioning for 30 s and the weakest after 45 s treatment. Conclusion: The phosphoric acid application time has an effect on the quality and strength of the enamel - bracket bond.